Data for outcome payments or information for care? A sociotechnical analysis of the management information system in the implementation of a social impact bond. Issue 3 (2nd April 2020) - Jamieson, David; Wilson, Rob; Martin, Mike; Lowe, Toby; Kimmitt, Jonathan; Gibbon, Jane; French, Max
ABSTRACT: Social Impact Bonds (SIBs) are a policy intervention designed to explicitly link the activity of social interventions to outcome payments. Despite a burgeoning literature on SIBs there is a lack of evidence in relation to the information system characteristics and accounting mechanisms of SIBs. Applying a multi-dimensional sociotechnical lens to a case study of a SIB allows us to reveal the current problematic convergence of public management and information systems. The authors found that an information system within a SIB is introduced and adapted to increasingly prioritize the production of data for payment over documenting care accounts to support improved provision. The ﬁndings of this paper also suggest that claims of SIBs as an innovation are limited as they are subject to the familiar problems of New Public Management practice, in the way they shape the design and use of the data in governance, management and service delivery practices. IMPACT: Social Impact Bonds (SIBs) have been positioned as an innovative vehicle to improve health and social outcomes through the use of externally provided funding. Although the debate about the viability and robustness of SIBs continues, no focus has been given to the informational requirements that are mandated in order to ensure that outcomes are being achieved—and therefore enable payment. The authors challenge that the data that is being collected by SIBs is in essence for the purposes of financial accounting rather than demonstrating improvements in the quality of care.